2019
DOI: 10.1002/anie.201909069
|View full text |Cite
|
Sign up to set email alerts
|

A Polymer Solution To Prevent Nanoclustering and Improve the Selectivity of Metal Nanoparticles for Electrocatalytic CO2 Reduction

Abstract: CO2‐Reduktion. Polymere NHC‐Liganden verbessern die Katalyseeffizienz und Lebensdauer von Au‐ und Pd‐Nanokatalysatoren zur CO2‐Elektroreduktion, wie B. Liu, J. He et al. im Forschungsartikel auf S. 15981 ff. zeigen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 58 publications
2
84
0
Order By: Relevance
“…[74,75] Strongly bound carbene based ligands were instead shown to stabilize the morphology of these electrocatalysts, leading to enhanced stability for selective CO formation. [76]…”
Section: Methodsmentioning
confidence: 99%
“…[74,75] Strongly bound carbene based ligands were instead shown to stabilize the morphology of these electrocatalysts, leading to enhanced stability for selective CO formation. [76]…”
Section: Methodsmentioning
confidence: 99%
“…Common ligands such as thiols or amines are readily electrodesorbed, which leads to sintering and coagulation of Au, Pd, and Ag nanoparticles . Strongly bound carbene based ligands were instead shown to stabilize the morphology of these electrocatalysts, leading to enhanced stability for selective CO formation …”
Section: Mitigation Strategies: Towards Stable Electrocatalystsmentioning
confidence: 99%
“…It has been demonstrated that NHC ligands have the ability to enhance nanocrystal catalyst stability and increase nanocrystal catalyst activity and/or selectivity. [9][10][11][12] NHC-stabilized nanocrystals have been shown to display catalytic activity toward, for example, hydrogenations and semihydrogenations, 9,[12][13][14] lactonization, 10 asymmetric arylations, 15 Buchwald-Hartwig aminations, 16 and cross-coupling reactions. 15 NHC-stabilized nanocrystals have also been shown to be competent electrocatalysts for CO2 reduction.…”
Section: Introductionmentioning
confidence: 99%
“…15 NHC-stabilized nanocrystals have also been shown to be competent electrocatalysts for CO2 reduction. 11,17 For example, Cao et al investigated the use of NHC-stabilized Au nanocrystals as electrocatalysts for the reduction of CO2 to CO. Interestingly, the Au nanocrystal catalyst with surface-bound carbene ligands exhibited a higher Faradaic efficiency for CO2 reduction to CO than did bare (or ligand-less) Au nanoparticles; it was further shown that the NHC affected the mechanistic pathway of catalysis. 17 Despite the proven benefits of applying NHC ligands to nanocrystal catalysts, they have thus far only been supported on metal nanocrystal catalysts (e.g., Ru, Au, Pt, Pd, Cu).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation